Limited evidence for sympathetic neural overactivation in older patients with type 2 diabetes mellitus - Heusser, Karsten; Tank, Jens; Diedrich, André; Fischer, Annelie; Heise, Tim; Jordan, Jens (Frontiers in Neuroscience, 2023)
Mechanistic studies suggested that excess sympathetic activity promotes arterial hypertension while worsening insulin sensitivity. Older patients with type 2 diabetes are at particularly high cardiovascular and metabolic risk. However, data on sympathetic activity in this population is scarce. We studied 61 patients with type 2 diabetes mellitus (22 women, 39 men). They had to have diabetes for at least 2 years, an age of 50-80 years, an HbA1c of 6.5-10%, a BMI of 25-40 kg/m², had to be treated with stable doses of metformin only. We recorded ECG, finger and brachial blood pressure, and muscle sympathetic nerve activity (MSNA). MSNA was 37.5±2.5 bursts/min in women and 39.0±2.0 bursts/min in men (p=0.55). MSNA expressed as burst incidence was 52.7±2.0 bursts/100 beats in women and 59.2±3.1 bursts/100 beats in men (p=0.21). Five out of 39 men (12.8%) and two out of 22 women (9.1%) exhibited resting MSNA measurements above the 95th percentile for sex and age. In the pooled analysis, MSNA was not significantly correlated with systolic blood pressure, diastolic blood pressure, body mass index, waist circumference, body composition or HbA1c (r2 < 0.02, p>0.26 for all). We conclude that relatively only few older patients with type 2 diabetes mellitus exhibit increased MSNA. The large interindividual variability in MSNA cannot be explained by gender, blood pressure, body mass index, or glycemic control.